PEDAGOGICAL COORDINATORS’ PERCEPTIONS ON DRUG USAGES AMONGST YOUTH AND ADULT EDUCATION STUDENTS FROM A LOCAL BRAZILIAN PUBLIC SCHOOL - JUNIOR, FRANCISCO MARCIO (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2022)
This paper presents the research findings obtained through a study as part of the Master’s dissertation in Education. Its overall aim was to comprehend the pedagogical coordinators’ perceptions on drug use among Youth and Adult Education (YAE)  students from a local public school in Distrito Federal - Brazil. Regarding its specific objectives, the research aimed at learning the pedagogical coordinators’ professional, biographic and education background; identifying their perceptions on drug use among those students as well as analysing how their perceptions affect how they adreess these issues. In order to achieve its purpose, we used the qualitative methodology (ZANETTE, 2017), the narrative interviewing (WELLER & ZARDO, 2013) was used as a method of qualitative data collection along with the content analysis method (BARDIN, 2009). Findings from other researchers have shown that drug criminalization has been used as a way of maintaining historically constructed inequalities. Lastly, after analysing the data collected, we noted that most pedagogical coordinators at times enhance stereotypes related to drug users and still believe in the efficiency of the current repressive drug policy. On the other hand, they realize that low achievement and violence are more associated with social vulnerability than drug use.
Keywords: Drug use at school; Youth and Adult Education; Pedagogical coordination.